Journeys to polyglotism: a case study of French, Spanish, and Japanese tourist guides - Dika Pranadwipa Koeswiryono; Francisca Titing Koerniawaty (Journal of Applied Studies in Language, 2021)
The study aimed at discovering the process through which three tourist guides of French, Spanish, and Japanese acquired different foreign languages. The data was taken through in-depth interviews to explore the motivation that drove their language learning, the language interference, the technique they used to self-teach themselves the language, and their immersion in the language’s native country. The recorded interviews were then transcribed and analyzed through data reduction, data display, and verification drawing. The results were then given to the subjects to ensure trustworthiness and to verify the researcher’s interpretation of the interview. The study found that 1) one of the most crucial factors of language learning success was strong motivation, which led to consistency and risk-taking attitude; 2) a significant growth of language mastery took place when the subjects spent extended time in the language’s native country; 3) both formal classroom instruction and informal independent learning were essential for their language improvement; 4) the subjects proactively consulted the native speakers to improve their vocabulary inventory, to correct inaccuracies or to gain new language expressions; and 5) due to the different nature of the languages they were learning, each subject had a diverse view on grammar and language interference. In pedagogical implication, teachers could foster students’ willingness to learn with either instrumental motivation, i.e. by raising awareness of the benefit of foreign language ability, or with integrative motivation, i.e. by raising students’ interest in the culture or people whose language was being studied. Besides, language learners, or language teachers, might reflect on this research to complement formal-classroom learning with a large degree of informal-independent learning.